Continuum Reverberation Mapping of AGN Accretion Disks - Fausnaugh, Michael M.; Peterson, Bradley M.; Starkey, David A.; Horne, Keith; , the AGN STORM Collaboration (Frontiers in Astronomy and Space Sciences, 2017)
We show recent detections of inter-band continuum lags in three AGN (NGC~5548, NGC~2617, and MCG+08-11-011), which provide new constraints on the temperature profiles and absolute sizes of the accretion disks. We find lags larger than would be predicted for standard geometrically thin, optically thick accretion disks by factors of 2.3 to 3.3. For NGC~5548, the data span UV through optical/near-IR wavelengths, and we are able to discern a steeper temperature profile than the $T\sim R^{-3/4}$ expected for a standard thin disk . Using a physical model, we are also able to estimate the inclinations of the disks for two objects. These results are similar to those found from gravitational microlensing of strongly lensed quasars, and provide a complementary approach for investigating the accretion disk structure in local, low luminsoity AGN.